Gender Features of Coping Strategies in Men and Women - Olga A. Ovsyanik; Albina A. Nesterova; Natalia V. Sidyacheva (RUDN Journal of Psychology and Pedagogics, 2022)
The effectiveness of coping behavior depends not only on a successful strategy but also on the individual characteristics of a person. Age, sex, intelligence, social status, gender identity - all these influence the coping ability and resilience of an individual. In mo- dern psychological research, there is some confusion between the concepts of ‘sex’ and ‘gender.’ Despite numerous studies on male and female coping strategies, gender differences in coping behavior are still poorly understood. The purpose of the study was to analyze gender-specific coping strategies of middle-aged men and women. Russian men and women (N = 286) were divided by gender (masculine, androgynous, feminine). The research was made using The Bem Sex-Role Inventory (BPRT) and Lazarus Folkman’s Test Ways of Coping Questionnaire (WCQ). This study employed a cross-sectional design. Differences among the groups were assessed using the Kruskal - Wallis H test, Mann - Whitney U test and Student t-test. The specificity of coping behavior was found to be determined by the gender identity of the study participants. The results of the present study support the gender differences hypothesis, since people with differences in biological sexual identity (male and female) use gender-specific coping strategies (masculine, feminine, or androgynous) if their gender orientations are the same. The research of masculinity, androgyny and femininity can become an important step in the long-term study of coping behavior and the basis for a better understanding of the dynamics of human behavior in a stressful situation.